Design Of Compressed Natural Gas Mixer Using Computational Fluid Dynamics - D., Ramasamy; Samykano, Mahendran; K., Kadirgama (2010)
The usage of natural gas is ever increasing with environment consciousness ever increasing. A general bi-fuel CNG system is analyzed on a new two-stroke engine. The mixer of CNG is to be designed for the new two-stroke gasoline engine. Mixer design is crucial to meter the flow of natural gas into the combustion chamber. With this the amount of gas can be controlled for different engine speeds and loads. To reduce the time to design computational fluid dynamics (CFD) is used to get the desired flow condition inside the mixer. Calculation is done for the initial sizing of the throat of the mixer and later is simulated to obtain the best flow characteristics. Different preliminary design is to get the best shape of the mixer. With the help of CFD the best shape is taken for fabrication. The initial calculation for sizing is based on the stoichiometry of the fuel and general fluid dynamic equations.